2017
DOI: 10.1177/0308022616680368
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a supportive housing program for homeless adults with mental illness and substance use: A two-group controlled trial

Abstract: Introduction: The purpose of this study was to assess the effectiveness of a housing transition program for homeless shelter residents with chronic mental illness and substance use. Method: A two-group controlled study design was used to assess the program, with 10 participants in an intervention group and 10 in a control group. Goal attainment scaling and quality of life ratings were used pre-and post-intervention to determine if a statistically significant difference existed between groups at post-interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Three studies investigated the effects of skills/knowledge acquisition interventions on goal-directed behaviors and reported improvements (Chapleau et al, 2012;Gutman & Raphael-Greenfield, 2017;Quinney & Richardson, 2014). The SMART program helped people transition from shelter services to housing by providing training in independent living and wellness (Gutman & Raphael-Greenfield, 2017). Six months after completing the program, compared to the control group who exclusively received shelter-based supportive services, SMART program participants' goal-attainment improved (p < .05) with a large effect size (d = 1.34).…”
Section: Behavioral Componentmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies investigated the effects of skills/knowledge acquisition interventions on goal-directed behaviors and reported improvements (Chapleau et al, 2012;Gutman & Raphael-Greenfield, 2017;Quinney & Richardson, 2014). The SMART program helped people transition from shelter services to housing by providing training in independent living and wellness (Gutman & Raphael-Greenfield, 2017). Six months after completing the program, compared to the control group who exclusively received shelter-based supportive services, SMART program participants' goal-attainment improved (p < .05) with a large effect size (d = 1.34).…”
Section: Behavioral Componentmentioning
confidence: 99%
“…Several studies that examined the effect of competency-building interventions on goal-directed behaviors were delivered in settings where a variety of services were simultaneously available to participants. These additional services included CM (Chapleau et al, 2012) and occupational, recreational, and psychiatric support (Gutman & Raphael-Greenfield, 2017), which may have contributed to, or interacted with, the positive effect of the competencybuilding elements on behavioral PE indicators.…”
Section: Behavioral Componentmentioning
confidence: 99%
“…Studies identifying valued occupations of homeless individuals revealed varied priorities and goals, with attention to survival, identity and social connectedness, and self-care (Chapleau et al, 2011;Illman et al, 2013;Marshall et al, 2017;Muñoz et al, 2006;Salsi et al, 2017;Thomas et al, 2017). This population can benefit significantly from access to occupational therapy in order to develop functional living skills, address underlying cognitive deficits, increase self and health management skills, and to more easily transition to and maintain independent living through occupational engagement (Gutman & Raphael-Greenfield, 2017;Helfrich & Fogg, 2007;Roy et al, 2017;Thomas et al, 2017). Current evidence additionally supports the effectiveness of occupational therapy interventions to address chronic health conditions, mental health diagnoses, and brain injury; supported interventions also include independent living, and cognitive and self-management skill development (Connolly et al, 2019;Gibson et al, 2011;Ikiugu et al, 2017;Leland et al, 2016;Powell et al, 2016;Pyatak et al, 2018;Radomski et al, 2016;Schwartz et al, 2017;Swarbrick & Noyes, 2018;Thomas et al, 2011).…”
Section: Literature Review Occupational Therapy and Homelessnessmentioning
confidence: 99%
“…Supporting individuals to overcome occupational performance difficulties is the traditional territory for many occupational therapists. The profession is developing its practice in the area of homelessness and there are occupational therapy interventions described in the literature (Gutman & Raphael-Greenfield, 2017;Helfrich, Aviles, Badiani, Walens, & Sabol, 2006). Notably, although the value of engaging in meaningful occupations for people who are homeless is well recognised in the occupational science literature, this is not so well reflected in the interventions described to date.…”
Section: Micro Level -Interactions With Individualsmentioning
confidence: 99%
“…In line with the increase in numbers of people experiencing homelessness, there is a growing field of practice and research in occupational therapy and occupational science related to homeless persons. This includes work around meaning and well-being (Cunningham & Slade, 2017;Marshall, Lysaght, & Krupa, 2017;Thomas, Gray, & McGinty, 2017) as well as interventions (Gutman & Raphael-Greenfield, 2017;Gutman, Raphael-Greenfield, & Simon, 2015;Lloyd, Hilder, & Williams, 2017). These are positive contributions for understanding occupation for people who are marginalised and the valuable role occupational therapy can play.…”
Section: Introductionmentioning
confidence: 99%